Sledování protinádorové bunecné imunitní odezvy u nemocných s renálním karcinomem, porucha proliferace T-lymfocytů - Lukesová, S; Vroblová, V; Hlávková, D; Kopecký, O; Vokurková, D; Morávek, P; Safránek, H; Soucek, P (Vnitrni lekarstvi, 2008)
INTRODUCTION: When checking tumour growth, a number of observations indicate that the immune system plays a significant role in patients with renal cell carcinoma (,,RCC"). Infiltration by lymphocytes (tumour infiltrating lymphocytes, "TILs") is more prevalent in RCC than any other tumours. T lymphocytes are the dominant population of TIL cells. Views concerning the role ofT lymphocytic subpopulations, B lymphocytes and NK cells in an anti-tumour response are not established. AIM: The aim is to determine the phenotype and activation of lymphocytic cells and to compare their representation in tumour stroma (TIL), peripheral blood (PBL) and renal vein blood in patients with RCC. PATIENTS AND METHODS: The samples of peripheral blood taken from the cubital and renal veins and tumour stroma cells were obtained from 60 patients in the course of their surgeries carried out due to primary RCC. TILs were isolated from mechanically disintegrated tumour tissue. Immunophenotype multiparametric analysis of PBL and TILs was carried out. Their surface and activation characteristics were determined by means of flow cytometer. RESULTS: CD3+ T lymphocytes (70.4%) were the main population of TILs. The number of CD3+/CD8+ T lymphocytes was significantly higher in TILs, 39.7% (p < 0.01), while CD4+ T lymphocytes were the majority population in peripheral blood, 41.35% (p < 0.001). The representation of CD3+/69+ T lymphocytes was significantly higher in TILs, 32.05%, compared to PBL (p < 0.001). On the contrary, the numbers of CD3+/CD25+, CD8+/57+ and CD4+/RA+ (naive CD4+ T lymphocytes) were higher in PBL (p < 0.001). The differences in representation of (CD3+/16+ 56+) NK cells and CD3+/DR+ T cells in TILs and PBL were not significant. CONCLUSION: The above-mentioned results prove that the characteristics and intensity of anti-tumour responses are different in compared compartments (tumour/PBL). CD3+/CD8+ T lymphocytes are the dominant lymphocytic population of TILs. The knowledge of phenotype and functions ofeffector cells, which are responsible for anti-tumour response, are the basic precondition for understanding the anti-tumour immune response and the cause of its failure.
Keywords: nádory ledvin; Male; Lymphocytes, Tumor-Infiltrating; karcinom z renálních buněk; Lymphocyte Subsets; Adult; Kidney Neoplasms; Aged; dospělí; mužské pohlaví; senioři; Flow Cytometry; senioři nad 80 let; průtoková cytometrie; lidé; ženské pohlaví; Humans; Aged, 80 and over; Carcinoma, Renal Cell; Female; tumor infiltrující lymfocyty; lidé středního věku; podskupiny lymfocytů; Middle Aged